2008
DOI: 10.1590/s0066-782x2008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência cardíaca com fração de ejeção preservada e com disfunção sistólica na comunidade

Abstract: SummaryBackground: In developed countries, heart failure with preserved ejection fraction (HFpEF) is more prevalent than heart failure with reduced ejection fraction (HFrEF) in the community. However, it has not been completely established if this fact is also observed within our community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
13
0
4
Order By: Relevance
“…When analyzing this study, it can be observed that the prevalence of DM (16.6%) was less significant, which can explain the lower occurrence of ischemic cardiomyopathy 19 .…”
Section: The Study By Latado Et Almentioning
confidence: 73%
See 1 more Smart Citation
“…When analyzing this study, it can be observed that the prevalence of DM (16.6%) was less significant, which can explain the lower occurrence of ischemic cardiomyopathy 19 .…”
Section: The Study By Latado Et Almentioning
confidence: 73%
“…The main guidelines for the management of HF 1,8,19,26 recommend, as the classic treatment, the sue of diuretics, ACEI or ARB and beta-blockers, but the etiology of HF and its intensity seem to influence the prescription of these drugs 13 .…”
Section: The Study By Latado Et Almentioning
confidence: 99%
“…The confirmation of the diagnosis required other echocardiographic measurements, such as the following: indexed LV mass > 122 g/m 2 , for women, and > 149 g/m 2 , for men; and ratio between early and late LV filing velocity (E/A ratio) lower than 0.5, with a deceleration time of the E wave greater than 280 m/s, for individuals over 50 years of age. In addition to the echocardiographic criteria, a BNP level greater than 200 pg/mL was also used.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies on heart failure (HF) have confirmed that HF with preserved ejection fraction (HFPEF) is more prevalent than HF with reduced ejection fraction (HFREF) [1][2][3] . The pathophysiological model focuses on the presence of diastolic dysfunction, subsequent to abnormalities of relaxation or increased left ventricular (LV) stiffness, which retrogradely produces an elevation in the mean left atrial (LA) pressure, causing structural and functional changes in that chamber 4 …”
Section: Introductionmentioning
confidence: 99%
“…The advantage of these studies is to obtain data from non-selected populations, differently from studies carried out in tertiary environments, where more severe patients are treated. A recent national study confirmed that, in the studied community, there was a predominance of HFNEF in relation to HFDEF 28 , which differs from what has been observed in Reference Services for HF.…”
Section: Introductionmentioning
confidence: 46%